Pengaruh ROA, ROE, dan NPM terhadap Return Saham Syariah pada Perusahaan Barang Baku di Jakarta Islamic Index - Vanessa NurulAnnisa; Sri Rahma; Laily Ifazah (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to examine the effect of Return on Assetss, Return on Equity, and Net Profit Margin on stock Return s of basic materials sector companies listed in the Jakarta Islamic Index (JII) during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from companies’ annual financial statements and stock price data. The sample was selected using purposive sampling, resulting in six companies that met the research criteria. Panel data regression analysis was conducted using EViews version 13. The findings show that ROA, ROE, and NPM individually do not have a significant effect on stock Return s. In addition, simultaneously, ROA, ROE, and NPM also do not have a significant effect on stock Return s of basic materials sector companies listed in the JII during the 2020–2024 period. The findings suggest that investors should not rely exclusively on profitability ratios as the basis for investment decisions, but should also take into account other factors, including business risk, the stability of corporate performance, and prevailing economic conditions.